Temperature and impurity concentration effects on upconversion luminescence in LaInO₃ doped with Er³⁺ - Sarakovskis, A.; Grube, J.; Strals, K.; Krieke, G.; Springis, M.; Mironova-Ulmane, N.; Skvortsova, V.; Yukhno, L.A.; Bashkirov, E.K. (Физика низких температур, 2016)
In this paper a novel method for synthesis of LaInO₃:Er³⁺ is reported and upconversion luminescence properties of the synthesized material at different temperatures (9–300 K) are studied. The samples were prepared by co-precipitation and subsequent heat treatment of lanthanum, indium and erbium hydroxides. It is shown that the excitation at 980 nm leads to a strong green upconversion luminescence in the material. At the concentrations above 0.1 mol. % of Er³⁺ the energy transfer upconversion mechanism of the luminescence becomes evident. Further increase of Er³⁺ content in the material leads to higher red-to-green upconversion luminescence intensity ratio. The mechanisms responsible for the observed variation are discussed.